Peran Ulama dan Tokoh Ormas Muhammadiyah Dalam Menangkal Golput Perspektif Fikih Siyasah - A, Abriansyah; Shuhufi, Muhammad; Amin, Abd. Rauf Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The phenomenon of abstention from voting, known as golput, which refers to the behavior of not voting in elections, is a significant concern in the context of political participation in Indonesia. Muhammadiyah, as one of the largest Islamic mass organizations in Indonesia, holds a substantial influence in the social and political life of Muslims. This article examines the role of ulama and Muhammadiyah figures in countering golput from the perspective of fiqh siyasah, a branch of Islamic jurisprudence that governs public administration and policy. The research method used is descriptive qualitative with a literature study approach and in-depth interviews with ulama and Muhammadiyah figures. The findings indicate that ulama and Muhammadiyah figures play a strategic role in raising political awareness among the ummah through da’wah, political education, and persuasive approaches based on Islamic values. From the perspective of fiqh siyasah, political participation through elections is viewed as a collective obligation (fardhu kifayah) that must be carried out to achieve public welfare. Thus, the role of ulama and Muhammadiyah figures in countering golput not only contributes to increasing political participation but also strengthens democracy and socio-political stability in Indonesia.